Spatially evaluating a network of plans and flood vulnerability using a Plan Integration for Resilience Scorecard: A case study in Feijenoord District, Rotterdam, the Netherlands. (November 2018) - Malecha, Matthew L.; Brand, A.D.; Berke, Philip R.
Highlights: Integrating hazard mitigation is a critical part of effective planning for resilience. The Plan Integration for Resilience Scorecard allows spatial evaluation of community networks of plans. Resilience is generally supported in Feijenoord District, Rotterdam, but conflicts do exist. The scorecard method reveals opportunities for stronger plan integration. Abstract: Rising damages from hazard events have led to calls for innovative research on resilience. Consistent integration of mitigation policies throughout a community's network of plans is increasingly seen as essential for effective resilience planning. To better understand coordination and conflicts in policy responses to flood hazards, this study evaluates a district in the city of Rotterdam, the Netherlands, using the Plan Integration for Resilience Scorecard method. An internationally recognized leader in resilience and water management, Rotterdam is nevertheless vulnerable to flooding, especially in a changing climate. Findings demonstrate that even a place as proactive in resilience policy as Rotterdam can benefit from the perspective gained using the scorecard technique. Although resilience is generally supported throughout the study area, conflicts remain. The scorecard reveals inconsistencies and opportunities to further reduce flood vulnerability by 'mainstreaming' resilience policies in the most influential plans.